Arterial thromboembolism in patients with sick sinus syndrome: prediction from pacing mode, atrial fibrillation, and echocardiographic findings. Issue 4 (1st April 1999) - Andersen, H R; Nielsen, J C; Thomsen, P E B; Thuesen, L; Pedersen, A K; Mortensen, P T; Vesterlund, T
Abstract : OBJECTIVE: To evaluate whether thromboembolism in sick sinus syndrome can be predicted by pacing mode, atrial fibrillation, or echocardiographic findings. METHODS: Patients were randomised to single chamber atrial (n = 110) or ventricular (n = 115) pacing. They were divided into subgroups with and without brady-tachy syndrome at time of randomisation. The occurrence of atrial fibrillation and thromboembolism during follow up were investigated and compared with echocardiographic findings. RESULTS: The annual risk of thromboembolism was 5.8% in patients with brady-tachy syndrome randomised to ventricular pacing, 3.2% in patients without brady-tachy syndrome randomised to ventricular pacing, 3% in patients with brady-tachy syndrome randomised to atrial pacing, and 1.5% in patients without brady-tachy syndrome randomised to atrial pacing. In atrial paced patients without brady-tachy syndrome at randomisation and without atrial fibrillation during follow up, the annual risk of thromboembolism was 1.4%. Left atrial size measured by M mode echocardiography was of no value in predicting thromboembolism. CONCLUSIONS: Arterial thromboembolism in patients with sick sinus syndrome is very common and is associated primarily with brady-tachy syndrome at randomisation and with ventricular pacing. The risk of thromboembolism is small in atrial paced patients in whom atrial fibrillation has never been documented.